Ontogeny, Phylotypic Periods, Paedomorphosis, and Ontogenetic Systematics - Martynov, Alexander; Lundin, Kennet; Korshunova, Tatiana (Frontiers in Ecology and Evolution, 2022)
The key terms linking ontogeny and evolution are briefly reviewed. It is shown that their application and usage in the modern biology are often inconsistent and incorrectly understood even within the “evo-devo” field. For instance, the core modern reformulation that ontogeny not merely recapitulates, but produces phylogeny implies that ontogeny and phylogeny are closely interconnected. However, the vast modern phylogenetic and taxonomic fields largely omit ontogeny as a central concept. Instead, the common “clade-” and “tree-thinking” prevail, despite on the all achievements of the evo-devo. This is because the main conceptual basis of the modern biology is fundamentally ontogeny-free. In another words, in the Haeckel’s pair of “ontogeny and phylogeny,” ontogeny is still just a subsidiary for the evolutionary process (and hence, phylogeny), instead as in reality, its main driving force. The phylotypic periods is another important term of the evo-devo and represent a modern reformulation of Haeckel’s recapitulations and biogenetic law. However, surprisingly, this one of the most important biological evidence, based on the natural ontogenetic grounds, in the phylogenetic field that can be alleged as a “non-evolutionary concept.” All these observations clearly imply that a major revision of the main terms which are associated with the “ontogeny and phylogeny/evolution” field is urgently necessarily. Thus, “ontogenetic” is not just an endless addition to the term “systematics,” but instead a crucial term, without it neither systematics, nor biology have sense. To consistently employ the modern ontogenetic and epigenetic achievements, the concept of ontogenetic systematics is hereby refined. Ontogenetic systematics is not merely a “research program” but a key biological discipline which consistently links the enormous biological diversity with underlying fundamental process of ontogeny at both molecular and morphological levels. The paedomorphosis is another widespread ontogenetic-and-evolutionary process that is significantly underestimated or misinterpreted by the current phylogenetics and taxonomy. The term paedomorphosis is refined, as initially proposed to link ontogeny with evolution, whereas “neoteny” and “progenesis” are originally specific, narrow terms without evolutionary context, and should not be used as synonyms of paedomorphosis. Examples of application of the principles of ontogenetic systematics represented by such disparate animal groups as nudibranch molluscs and ophiuroid echinoderms clearly demonstrate that perseverance of the phylotypic periods is based not only on the classic examples in vertebrates, but it is a universal phenomenon in all organisms, including disparate animal phyla.